Caregiver qualities, family closeness, and the well-being of adolescents engaged in the child welfare system. (February 2017) - Cederbaum, Julie A.; He, Amy S.; Fulginiti, Anthony; Sullivan, Kathrine; Krauss, Max D.; Amutah, Ndidi; Pohle, Cara
Abstract: Children who come into contact with the child welfare system are at greater risk of experiencing internalizing and externalizing behaviors. This secondary analysis of the National Survey of Child and Adolescent Well-Being explored how caregiver characteristics and behaviors, and caregiver–child closeness influence these outcomes over time. The final sample was 877 caregiver and adolescent (11–17 years old) dyads. Weighted multivariate regression analyses were performed. Caregiver characteristics associated with depressive symptoms included age and education; caregiver health was not associated with internalizing and externalizing behaviors. For adolescents, being female, older, or Hispanic was associated with internalizing behaviors. Although not significant for externalizing behaviors, caregiver–adolescent closeness was protective against internalizing behaviors. Understanding factors that contribute to the mental health of child-welfare-exposed adolescents has far-reaching implications for family-based interventions with child-welfare-involved youth. Highlights: Adolescent characteristics were associated with behaviors in bivariate models. Closeness to caregiver was associated with behaviors in bivariate models. Caregiver age and education predicted internal and external symptoms in adolescents. Adolescent age, gender, and ethnicity predicted internalizing behaviors. Closeness remained predictive of depression, internal, and external behaviors.